PEMIKIRAN KI BAGOES HADIKOESOEMO MENGENAI KONSEP NEGARA - Wildan Nurul Fajar (Universitas Muhammadiyah Purwokerto, 2019)
This research aims to describe, analyze, and formulate Ki Bagoes Hadikoesoemo's political thinking about the State of Indonesia. This study uses a critical character study method which is one of the types of qualitative research. Data collection and information techniques used include study documentation and interviews. The results of the study showed that Ki Bagoes Hadikoesoemo had an important role in the formulation of the basic state of Indonesia in the Jakarta Charter. Ki Bagoes Hadikoesoemo had an important role in the first Sila Pancasila change as it is now. In Muhammadiyah, Ki Bagoes Hadikoesoemo has put Baldatun Thayyibatun Wa Rabbun Ghafur as the foundation of Muhammadiyah's ideals in developing the country as stated in the articles of association Muhammadiyah's. Keywords: Political Thought, Ki Bagoes Hadikoesoemo, State Concept, Muhammadiyah